Pride or backlash? Public attitudes towards the Spanish women`s national football team - Moscoso-Sánchez, D.; Pasadas-del-Amo, S.; Ramis-Moyano, R.; Trujillo-Carmona, M. (Frontiers in Sports and Active Living, 2025)
Introduction: In August 2023, Spain's Women's National Football Team won the FIFA Women's World Cup for the first time. Beyond sporting success, this victory became a catalyst for intense public debate on gender equality and athlete activism. Shortly after the tournament, two events brought these issues to the forefront: the non-consensual kiss by the president of the Real Federación Española de Fútbol (RFEF), which triggered nationwide protests under the hashtag #SeAcabó ("It's over"), and a strike by players demanding better working conditions and higher wages. While these events deepened discussions about sexism in sport, they also revealed strong ideological divisions in Spanish society. This article examines how Spaniards perceived these events and the players` labour activism.